Does Eligibility for Tertiary Education Affect Crime Rates? Quasi-Experimental Evidence - Martin Nordin (Lund University, School of Economics and Management, Department of Economics, 2014)
This paper estimates a tertiary eligibility effect on crime for Sweden. The idea is that investment in higher education is a way of escaping youth inactivity and idleness, and, since youth inactivity is known to trigger crime, the self-incapacitation effect of higher education decreases crime rates. However, to invest in higher education, the individual has to meet the tertiary eligibility requirements in upper-secondary school. Tertiary eligibility may therefore affect crime rates. Evidence of an exogenous grade inflation in the eligibility rate is used to identify the tertiary eligibility effect. With the introduction of a goal-related grading system, the share with tertiary eligibility increased by more than 6 percentage points. Accordingly, during the period with grade inflation in the eligibility rate, crime rates fell, but, when the period of grade inflation was ended, the effect of tertiary eligibility on crime disappeared as well. Hence, when youth have the opportunity to invest in higher education, and thus escape unemployment or inactivity, their propensity to commit crime decreases.
Keywords: J20; K14; K42; 330; crime; education; tertiary eligibility